Russian Foreign Clergy in the 19th Century in Western Europe: General Tendencies and Peculiarities - Gogorian Kristina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to general tendencies and peculiarities of а special group of Russian clergy, located at the embassies in the countries of Western Europe. Formed in the Synodal period, this category of clergy was under a double jurisdiction. It obeyed both spiritual and secular authorities, represented by The Holy Synod and the Ministry of Foreign Aﬀairs. Therefore, the status of the foreign clergy was inﬂ uenced by many factors: religion, culture, politics, and diplomacy. The speciﬁcs of a particular region played important role. International relations of Russia and the country where service was held had inﬂuence on the foreign clergy. An Orthodox priest, as well as the diplomatic corps, was the representative of his country abroad; his duties often extended beyond Church life, and sometimes even acquired diplomatic skills. In addition, in all European countries, the position of the embassy priests was much diﬀerent from the clergy in the country. Special attention in the article is paid to education, oﬃcial and economic status, and other characteristics of the embassy clergy as a group. The evolution of this category took place during the 19th century. Church building was the main concern of the embassy clergy in the second half of the century, when Orthodox churches were built in diﬀerent parts of Europe, to acquaint the West with Russian culture and Eastern branches of Christianity.